Ultrathin TiO2-B nanowires with enhanced electrochemical performance for Li-ion batteries1. Issue 18 (14th May 2015) - Lan, Tongbin; Dou, Jie; Xie, Fengyan; Xiong, Peixun; Wei, Mingdeng
<x xml:space="preserve">Abstract</x> Ultrathin TiO2-B nanowires with the most open channels exhibited large reversible lithium-ion charge–discharge capacity, excellent cycling stability and high-rate capability.